History, memory, and state-sponsored violence : time and justice - Bevernage, Berber. (Routledge approaches to history, 2012)
"Modern historiography embraces the notion that time is irreversible, implying that the past should be imagined as something "absent" or "distant." Victims of historical injustice, however, in contrast, often claim that the past got "stuck" in the present and that it retains a haunting presence. History, Memory, and State-Sponsored Violence is centered around the provocative thesis that the way one deals with historical injustice and the ethics of history is strongly dependent on the way one conceives of historical time; that the concept of time traditionally used by historians is structurally more compatible with the perpetrators than the victims point of view. Demonstrating that the claim of victims about the continuing presence of the past should be taken seriously, instead of being treated as merely metaphorical, Berber Bevernage argues that a genuine understanding of the irrevocable past demands a radical break with modern historical discourse and the concept of time. By embedding a profound philosophical reflection on the themes of historical time and historical discourse in a concrete series of case studies, this project transcends the traditional divide between empirical historiography on the one hand and the so called theoretical approaches to history on the other. It also breaks with the conventional analytical philosophy of history that has been dominant during the last decades, raising a series of long-neglected big questions about the historical condition questions about historical time, the unity of history, and the ontological status of present and past programmatically pleading for a new historical ethics"--